FORMATION OF NANO- AND MICROSPHERULES OF MINERALS IN ORE DEPOSITS DEPENDING ON DEPTH OF HOST ROCK OCCURRENCE - Adushkin V.V.; Popel S.I.; Andreev S.N. (My University, 2006)
The cavitation and cavitation-ablation mechanisms of formation of mineral nano-and microspherules in hydrothermal fluids are considered. The formation conditions of nano-and microspherules were studied with regard to the depth of host rock occurrence on the basis of the theory describing the cavitation mechanism. It is shown that the temperature and pressure of hydrothermal fluid as functions of the depth of host rock occurrence may markedly affect the dimensions of cavitation bubbles, the temperature within them at the moment of greatest compression, and the time of bubble collapse in the fluid. the dimensions of nano-and microspherules produced by cavitation depend only slightly on the depth of host rock occurrence and are mainly controlled by the thermophysical properties of their constituents. Characteristic dimensions of nanospherules formed as a result of ablation from the surface of overheated material have been obtained. © Pleiades Publishing, Inc. 2006.